Estudo da importância do Gallus gallus como chamariz da Lutzomyia longipalpis (Diptera, Psychodidae, phlebotominae) no ambiente doméstico e caracterização de fonte alimentar do flebotomíneo na localidade de Preiçueira, município de São José de Ribamar-MA, em 2005. - Barros, Vera Lúcia Lopes (2006)
The Lutzomyia longipalpis vector of the Leishmania chagasi, etiológico agent of Leishmaniose American Visceral (LVA). One verified the hens influence in the distribution and longipalpis maintenance of Lutzomyia in the human environment. The study intra was carried through in environments and peridomicílio of 12 houses in the Preiçueira city of Is Jose de Ribamar-MA, with the 06 lumisosas traps CDC of the 18 hs. It of the 512 flebótomos was studied relative abudancia and had been captured L.longipalpis, being 105 units in the houses without hen house and 407 in the houses with hen house. In the distance of the hen houses for the habitations human beings and the influence of the hens in the attraction of the vector for the intradomicílio. In this Goal the repetitions had been captured 36 added specimens. The effect of the hen house in the accessibility of the habitation human being for the flebótomos was resulted in 320 l L.longipalpis units of in the interior of an abandoned house, was observed that in the last night, with the addition of longipalpis females of L., 78.8% of the total sample were captured. For ends of comparison of the importance of the hen in the attraction of the Lutzomya longipalpis, hens had been carried through captures during 4 nights using only isca. One verified that the bird continued attracting the vector for the intradomicílio had been collected 55 specimens of this insect, in the first night with 5 (9%), second 16 (29%), third 16 (29%) and in the fourth night with 18 (33%) of the total sample. In all the carried through goals the hen was important in the attraction of flebotómo, more isca of females of the same species was the one that more attracted the Lutzomyia longipalpis for the interior of the domiciles.